2012
DOI: 10.1016/j.rmed.2012.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory physiotherapy can increase lower esophageal sphincter pressure in GERD patients

Abstract: 0922/09.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
5
2
1
Order By: Relevance
“…They found that respiratory exercise could result in LES pressure enhancement. 26 Studies that focused on the effects of PPIs on the reflux symptom showed that omeprazole could improve the QOL of the patients, but the QOL of the control group in the present study did not significantly change. Maybe the normal dosage of PPIs should be 40 mg daily to improve the QOL of the patients with reflux.…”
Section: Discussioncontrasting
confidence: 63%
“…They found that respiratory exercise could result in LES pressure enhancement. 26 Studies that focused on the effects of PPIs on the reflux symptom showed that omeprazole could improve the QOL of the patients, but the QOL of the control group in the present study did not significantly change. Maybe the normal dosage of PPIs should be 40 mg daily to improve the QOL of the patients with reflux.…”
Section: Discussioncontrasting
confidence: 63%
“…The extrinsic crural diaphragm surrounding LES is the other fundamental component to maintain the normal function of anti‐reflux defense line. Previous studies have demonstrated that inspiratory muscle training can increase LES pressure , decrease acid reflux assessed by pH‐metry, improve quality of life and reduce the PPI usage in GERD patients . In the current acute study, however, the elevation of LESP with STEA was not attributed to enhanced diaphragmatic pressure because STEA was performed before but not during the HRM test.…”
Section: Discussioncontrasting
confidence: 62%
“…More recently laryngeal rehabilitation therapies have been applied in cases of chronic cough associated with GERD, with significant symptom improvement [Pacheco et al 2013]. Carvalho de Miranda Chaves and colleagues [Carvalho de Miranda Chaves et al 2012] showed, by performing esophageal manometry, that inspiratory muscle training incremented LES pressure in patients with GERD after an 8-week program. Eherer and colleagues [Eherer et al 2012], in a randomized controlled study, showed that actively training the diaphragm muscle by breathing exercise, can improve reflux disease.…”
Section: Speech Therapy and Rehabilitation Techniquesmentioning
confidence: 99%